A REVERSE PHASE ULTRA PERFORMANCE LIQUID CHROMATOGRAPHY-PHOTO DIODE ARRAY ESTIMATION OF CAPTOPRIL AND HYDROCHLOROTHIAZIDE IN BULK AND PHARMACEUTICAL DOSAGE FORM - MANORANJANI, M.; T. N. V. S. S., SATYADEV; DAVID RAJU, M. (International Journal of Applied Pharmaceutics, 2024)
Objective: This investigation demonstrates a stability-indicating and reliable “Reverse Phase Ultra-Performance Liquid Chromatography (RP-UPLC)” method to simultaneously quantify Hydrochlorothiazide (HCTZ) and Captopril in the pharmaceutical dosage form. Methods: Hydrochlorothiazide and Captopril were separated by using C18 column (100 mm x 2.1 mm, 1.7μm) with an isocratic type of elution using mobile phase containing Acetonitrile+0.1% formic acid buffer (60:40), respectively with 0.2 ml/min flow rate. The wavelength used to detected at 210 nm to quantify Hydrochlorothiazide and Captopril. Results: Captopril and Hydrochlorothiazide peaks were eluted with fine resolution at retention times 0.772 min and 1.679 min, respectively. In 5-30 μg/ml concentration ranges for each Captopril and Hydrochlorothiazide, the calibration graphs were linear, with regression coefficients of 0.9998 and 0.9995, respectively. The suggested Ultra-performance liquid chromatography approach has been shown as sensitive, precise, robust, accurate, specific and stability, indicating through the resolution of Captopril and Hydrochlorothiazide from its degradation-based compounds. Conclusion: The established ultra-performance liquid chromatography technique was effectively extended to the evaluation of Captopril and Hydrochlorothiazide in the pharmaceutical dosage form, and the test results appeared satisfactory.